Feminist debates. Issues of theory and political practice - BRYSON, Valerie (Macmillan Pres LTD, 1999)
In this comprehensive study, Valerie Bryson draws on a wide range of theoretical, empirical and comparative material to provide a lucid account of feminist debates and the ways in which political disagreements stem from underlying theoretical assumptions. By disentangling questions of style and strategy from more profound disagreements, Bryson points the way to more effective forms of feminist political practice.